Evapotranspiration dynamics and effects on groundwater recharge and discharge at an arid waste disposal site. (October 2016) - Glenn, Edward P.; Jarchow, Christopher J.; Waugh, W. Joseph
Abstract: Deserts have been used for waste disposal due to presumed low groundwater recharge. The US Department of Energy is evaluating groundwater flow and contaminant transport at a former uranium mill site near Tuba City, Arizona. They developed a groundwater flow model to determine how fast contaminants were moving towards a downgradient stream, Moenkopi Wash, used to irrigate crops. We used remote sensing algorithms and precipitation (PPT) data to estimate ET and the ET/PPT ratios within the 3513 ha groundwater model domain (GMD) from 2000 to 2012. ET and PPT were nearly balanced (125 mm yr −1 and 130 mm yr −1, respectively). However, seasonal and interannual variability in ET and PPT were out of phase. Spatial variability in vegetation differentiated areas where ET was less than PPT (potential recharge areas) from those where ET exceeded PPT (potential discharge areas) within the GMD. ET estimates predicted that 0.2 million cubic meters per year of groundwater contributed to surface flows in Moenkopi Wash, supported by measurements of streamflow at the upstream and downstream boundaries of the GMD. Even small differences between ET and PPT can influence groundwater flow, hence land use practices that enhance discharge through ET can be part of an overall remediation strategy. Highlights: Desert have been used for waste disposal due to presumed low groundwater recharge. Evapotranspiration was measured over a wide area at a former arid uranium mill site. Over 3513 ha precipitation exceeded evapotranspiration by 3% inducing groundwater flow. It should not be assumed that contaminants can be safely stored in desert soils. Land management practices can impact net groundwater recharge or discharge.